2022
DOI: 10.1007/s11695-022-06346-9
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Pregnancies After Bariatric Surgery has No Impact on Children’s Health—a Nationwide Population-based Registry Analysis

Abstract: Purpose Bariatric surgery has a favorable effect on fertility in women. However, due to a lack of data regarding children’s outcomes, the ideal time for conception following bariatric surgery is unknown. Current guidelines advise avoiding pregnancy during the initial weight loss phase (12–24 months after surgery) as there may be potential risks to offspring. Thus, we aimed to analyze health outcomes in children born to mothers who had undergone bariatric surgery. The surgery-to-delivery interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Chao et al found that delivery during the 2 years after BS was not associated with an increased risk of surgical reinterventions [33]. Additionally, the surgery-to-delivery interval was found to have had no significant impact on the health outcome of children in the first year of life [34]. An important issue to be remembered is that women will become pregnant with a shorter TTC interval.…”
Section: Optimum Time-to-conception Interval After Bariatric Surgerymentioning
confidence: 99%
“…Chao et al found that delivery during the 2 years after BS was not associated with an increased risk of surgical reinterventions [33]. Additionally, the surgery-to-delivery interval was found to have had no significant impact on the health outcome of children in the first year of life [34]. An important issue to be remembered is that women will become pregnant with a shorter TTC interval.…”
Section: Optimum Time-to-conception Interval After Bariatric Surgerymentioning
confidence: 99%
“…Clinical guidelines recommend delaying pregnancy for 12–18 months after BS, until weight loss has stabilised and dietary intake is adequate, to prevent nutritional deficiencies [ 31 , 32 , 39 , 40 ]. Although studies that have evaluated early pregnancies have not consistently observed an increase in complications [ 36 , 37 , 41 ], a closer clinical follow-up is recommended in these cases.…”
Section: Bariatric Surgery and Pregnancymentioning
confidence: 99%